2008
DOI: 10.1007/s11357-007-9042-z
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in salivary protein carbonyl levels in normal and cognitively impaired human subjects

Abstract: Oxidative stress has been documented in tissues and biofluids of subjects with sporadic Alzheimer disease (AD) and mild cognitive impairment (MCI). The aim of this study was to determine whether (a) salivary protein carbonyls are elevated in AD and MCI subjects, (b) salivary protein carbonyl contents in these groups exhibit diurnal variation, and (c) apolipoprotein E ɛ4 (apoE ɛ4) carrier status impacts salivary carbonyl concentrations or rhythmicity in the AD and MCI cohorts. Unstimulated saliva was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Previously, significantly highest TBARS levels were observed in the morning hours [18]. On the other hand Su et al observed diurnal variations in salivary protein carbonyl concentrations with highest concentrations at 2:00 p.m. [50]. Significant daily variations were observed in salivary FRAP levels (F = 3.019, p < 0.01, ANOVA) representing antioxidant status.…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, significantly highest TBARS levels were observed in the morning hours [18]. On the other hand Su et al observed diurnal variations in salivary protein carbonyl concentrations with highest concentrations at 2:00 p.m. [50]. Significant daily variations were observed in salivary FRAP levels (F = 3.019, p < 0.01, ANOVA) representing antioxidant status.…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 81%
“…Assessment of circadian rhythm could be also valuable for optimization of therapeutic interventions according to expected redox homeostasis [50].…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 99%
“…Pandey observed an age-dependent increase in plasma protein carbonyl level (r=0.768) and protein carbonyls/ FRAP ratio (r=0.917), and plasma protein carbonyl levels were between 20 and 70 nmol/L (Pandey et al 2010). Su reported that the salivary protein carbonyl level among healthy adults was 1.80±0.15 nmol/mg (Su et al 2008), but he denied the relationship between levels of log protein carbonyls and age (Su et al 2012). Baltacioglu discovered that the average levels of serum and gingival crevicular fluid protein carbonyls were 1.22 and 1.10 nmol/mg (Baltacioglu et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…After collection, tubes with samples were kept at 4°C while further process must be done in 1 h. The tubes were centrifuged at 4000 rpm for 20 min at 4°C (Eppendorf Co., Hamburg, Germany), and the supernatants were gathered and stored in 1-mL aliquots for less than half a month ahead of detection. Samples mixed with blood or other visible impurities were discarded immediately, and each sample should not be frozen and thawed twice or more (Pandey et al 2010;Su et al 2008Su et al , 2009Su et al , 2012Zeng et al 2012). …”
Section: Sampling and Preparationmentioning
confidence: 99%
See 1 more Smart Citation